Beam-to-column connection using hollow steel section for precast concrete frames - Majid, Mohamad Zaki (2010)
The performance of precast concrete frames depends on the behaviour of connection. The configuration of connections between beam-to-column affects the constructability, stability, strength, flexibility and residual force in the structure. In addition, connections play a key role in the dissipation of energy and redistribution of loads. This paper describes the comparative study on testing between rigid and precast beam-to-column connections to obtain the important characteristics of the connections such as the load-displacement and moment-rotation relationship. The objective of the study is to propose a beam-to-column connection using hollow steel section for precast concrete frames and to determine experimentally the moment resistance and rotation of the proposed beam-to-column connection. In this study, three specimens comprised two precast concrete beam-to-column connection using hollow steel section and one rigid beam-to-column connection were considered. The behaviour of load displacement, moment rotation relationships and type of failure in connections are also investigated. The result indicates that the precast connection using hollow steel section provides very minimum moment resistance and hence the connection can be best model as pinned.